Cover Picture: 1, 2, 4‐Triazol‐5‐ylidenes versus Imidazol‐2‐ylidenes for the Stabilization of Phosphorus(I) Cations (Z. Anorg. Allg. Chem. 22/2016). Issue 22 (November 2016) - Elnajjar, Fawzia O.; Binder, Justin F.; Kosnik, Stephanie C.; Macdonald, Charles L. B.
Abstract : The cover picture illustrates the relative π‐acidity of two classes of N‐heterocyclic carbenes that have been employed to stabilize the usually very reactive P + ion. The background depicts the packing structure of the tetraphenylborate salt of a cation featuring a P + ion that is ligated by two 1, 4‐diisopropyl‐1, 2, 4‐triazol‐5‐ylidene (TAZ) groups (P atoms are gold, N atoms are blue, B atoms are red, C atoms are grey). Direct comparisons of the chemical and physical properties of salts of the cations featuring TAZ ligands and those of analogous P I cations stabilized by 1, 3‐diisopropylimidazol‐2‐ylidene (IMID) ligands were made using X‐ray crystallography, NMR spectroscopy and computational calculations. The data reveal a larger degree of π‐bonding across the C‐P‐C fragment in the case of the TAZ‐stabilized P I cations that is attributable to the greater π‐accepting ability of the TAZ group. More details are discussed in the article by Elnajjar et al. on pp.1251 ff .